Dielectric properties determination of a stratified medium - Yoiyod, Paiboon; Krairiksh, Monai (My University, 2015)
The method of detection of variation in dielectric properties of a material covered with another material, which requires nondestructive measurement, has numerous applications and the accurate measurement system is desirable. This paper presents a dielectric properties determination technique whereby the dielectric constant and loss factor are extracted from the measured reflection coefficient. The high frequency reflection coefficient shows the effect of the upper layer, while the dielectric properties of the lower layer can be determined at the lower frequency. The proposed technique is illustrated in 1-11 GHz band using 5 mm-thick water and 5% saline solution. The fluctuation of the dielectric properties between the high frequency and the low frequency, results from the edge diffraction in the material and the multiple reflections at the boundary of the two media, are invalid results. With the proposed technique, the dielectric properties of the lower layer can be accurately determined. The system is validated by measurement and good agreement is obtained at the frequency below 3.5 GHz. It can be applied for justifying variation of the material in the lower layer which is important in industrial process.
Keywords: Dielectric properties; Diffraction coefficient; Reflection coefficient; Stratified medium